2018
DOI: 10.1007/s11099-018-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lead on photosynthetic performance of waxberry seedlings (Myrica rubra)

Abstract: The photosynthesis was investigated 30 d after Pb treatment in Myrica rubra seedlings. The Pb treatment resulted in significantly increased Pb concentrations in shoots. Low Pb concentration exposure (≤2 mM) reduced the net photosynthetic rate (P N ), transpiration rate (E), and stomatal conductance (g s ) without affecting the intercellular CO 2 concentration (C i ), chlorophyll (Chl) content, and Chl fluorescence parameters. At 10 d after severe Pb treatment (≥4 mM), P N was inhibited and accompanied by Chl d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Heavy metals often occur in trace concentrations naturally, but they may be concentrated in certain areas as a result of anthropogenic activities including burning of fossil fuels, mining, application of fertilizers and pesticides, industrial wastes, and vehicle emissions. The excess heavy metals have been recognized to have a significant toxicity for animals, plants, microorganisms, and human beings, as well as for environment (Nagajyoti et al 2010, Sun et al 2010, Lee et al 2014, Shen et al 2017, He et al 2018. In southern China, lead (Pb) and zinc (Zn) were the most common heavy metal pollutants in soil (Sun et al 2010, Hladun et al 2016 and the concentrations of these two metals were much higher in this region than the standard criteria of the country (MEPC 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals often occur in trace concentrations naturally, but they may be concentrated in certain areas as a result of anthropogenic activities including burning of fossil fuels, mining, application of fertilizers and pesticides, industrial wastes, and vehicle emissions. The excess heavy metals have been recognized to have a significant toxicity for animals, plants, microorganisms, and human beings, as well as for environment (Nagajyoti et al 2010, Sun et al 2010, Lee et al 2014, Shen et al 2017, He et al 2018. In southern China, lead (Pb) and zinc (Zn) were the most common heavy metal pollutants in soil (Sun et al 2010, Hladun et al 2016 and the concentrations of these two metals were much higher in this region than the standard criteria of the country (MEPC 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this meta-analysis, we showed that toxic metals (Pb and Al) affect plant physiology by reducing photosynthetic activity. Although photosynthesis is important to determine plant vigor, it is very vulnerable to stress by toxic metals (He et al, 2018). Due to the toxicity of the metals, the photosynthetic apparatus is impaired, altering stomatal conduction, transpiration rate and the gas exchange associated with internal carbon.…”
Section: Discussionmentioning
confidence: 99%
“…Plants sensitive to toxic metal contamination, such as the Myrica genus, exhibit toxicity symptoms, indicating the presence of these elements in the environment. The plasma membrane can be affected by toxic metals, since it is the first to establish a relationship with these contaminants (He et al, 2018). Photosynthesis of plants exposed to toxic metal contamination is also compromised, since these elements can reduce the levels of chlorophyll and carotenoids due to the inactivation of the enzymes responsible for the biosynthesis of these pigments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations